Human herpesvirus type 6 and type 1 infection increases susceptibility to nonmelanoma skin tumors - Leite, J. L.; Stolf, Hamilton Ometto [UNESP]; Reis, N. A.; Ward, L. S. (Elsevier B.V., 2005)
In order to investigate herpesvirus (HHV) role in the susceptibility to skin cancer, we compared HHV6 and HHV1 incidence in DNA samples extracted from 120 lesions and 41 normal skin tissues. HHV6 (31.7%) and HHV1 (23.8%) were detected more frequently in skin cancer than in control individuals (14.6 and 5%, respectively) (P=0.0391 and P=0.00094, respectively). The risk of presenting basal cell carcinomas (BCC) was more than 3 times higher for HHV-6 infected patients (OR=3.182; 95% CI: 1.125-8.997). The risk for HHV-1 infected individuals of presenting BCC and squamous cell carcinomas was increased 8 and 6 times, respectively (OR=8.125; 95% CI: 1.735-38.043 and OR=6.290; 95% CI: 1.283-30.856, respectively). (c) 2004 Elsevier B.V.. All rights reserved.
Keywords: herpesvirus; cutaneous; cancer; infection; virus; susceptibility